2017
DOI: 10.1161/jaha.116.004264
|View full text |Cite
|
Sign up to set email alerts
|

Race‐Sex Differences in Statin Use and Low‐Density Lipoprotein Cholesterol Control Among People With Diabetes Mellitus in the Reasons for Geographic and Racial Differences in Stroke Study

Abstract: BackgroundStatin therapy is a cornerstone of cardiovascular disease risk reduction for people with diabetes mellitus. Past reports have shown race‐sex differences in statin use in general populations, but statin patterns by race and sex in those with diabetes mellitus have not been thoroughly studied.Methods and ResultsOur sample of 4288 adults ≥45 years of age with diagnosed diabetes mellitus who had low‐density lipoprotein cholesterol (LDL‐C) >100 mg/dL or were taking statins recruited for the Reasons for Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 38 publications
5
41
1
2
Order By: Relevance
“…50 Nevertheless, some studies found that women with T2DM were less likely to be prescribed statin (or lipidlowering treatment) when compared with male counterparts. 41,45,[52][53][54] Moreover, numerous observational and cross-sectional studies had shown that a lower proportion of women with T2DM were on target regarding LDL cholesterol when compared with men ( Table 2). 27-29,31-42,52,55-58 d Importantly, when mean LDL cholesterol levels (or the on-target percentage) were stratified according to statin therapy, women on statin therapy 54 and untreated women tended to have worse control of LDL cholesterol than men.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Nevertheless, some studies found that women with T2DM were less likely to be prescribed statin (or lipidlowering treatment) when compared with male counterparts. 41,45,[52][53][54] Moreover, numerous observational and cross-sectional studies had shown that a lower proportion of women with T2DM were on target regarding LDL cholesterol when compared with men ( Table 2). 27-29,31-42,52,55-58 d Importantly, when mean LDL cholesterol levels (or the on-target percentage) were stratified according to statin therapy, women on statin therapy 54 and untreated women tended to have worse control of LDL cholesterol than men.…”
Section: Hypertensionmentioning
confidence: 99%
“…41,45,[52][53][54] Moreover, numerous observational and cross-sectional studies had shown that a lower proportion of women with T2DM were on target regarding LDL cholesterol when compared with men ( Table 2). 27-29,31-42,52,55-58 d Importantly, when mean LDL cholesterol levels (or the on-target percentage) were stratified according to statin therapy, women on statin therapy 54 and untreated women tended to have worse control of LDL cholesterol than men. 32,27 The reasons for such a disparity are not completely understood, but it is possible that female sex per se confers higher LDL cholesterol levels.…”
Section: Hypertensionmentioning
confidence: 99%
“…Different previous studies evaluated the relationship between the gender and other coexisting diseases with DM. [5][6][7][8][9][10][11][12] In a study by Al-Salameh et al, the association between gender and control of diabetes and other cardiovascular risk factors in patients with type 2 DM were investigated. 6 In the study it was revealed that women were less likely to be smokers or ex-smokers, and less likely to have cardiovascular disease at the baseline than men.…”
Section: Discussionmentioning
confidence: 99%
“…Gamboa et al, evaluated the race and gender differences in statin use and LDL cholesterol control among the DM patients. 8 The recruited the patients with a LDL level >100 mg/dL, or were taking statins. In the study the authors divided the included patients into four groups which were white women, black women, white men, and black men, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation